PENINGKATAN KEAKTIFAN BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN THINK PAIR SHARE (TPS)(PTK Bagi Siswa Kelas X AK dan PM Semester Ganjil SMK Muhammadiyah 2 Surakarta Tahun Ajaran 2015/2016) - Endrayani, Dwi (2016)
This research aims to improve student's activity in mathematics learning thorough the Think Pair Share model study. This research is a classroom action research. The subject of this research are students and teacher of class X AK dan X PM SMK Muhammadiyah 2 Surakarta. The implementation of the actions research carried out for two cycles for four meetings. The techniques of collecting data was observation, documentation, test methods, and filed notes. To ensure the validity of data used triangulation, sources and field techniques. The techniques of analisis data are ata reduction, data presesntation, and verification of data. The results of the research shows that there are increasing of student activity on mathematics learning through Think Pair Share model study seen from the percentage of: (1) active student enquire, before action counted 8 student (26,67%), after action become 24 student (80,00%); (2) student tell opinion, before action counted 7 student ( 23,33%), after action become 22 student (73,33%); ( 3) student paying attention, before action counted 9 student (30,00%), after action become 26 student (86,67%). It can be concluded that the application of the Think Pair Share model study to the study of mathematics can improve students' activity.